Analisis Tingkat Kepentingan Berbagai Jenis Kriteria Moda, Pemakaian Metode AHP dalam Menentukan Moda Angkutan Umum di Bandar Lampung. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The local government of Bandar Lampung has done some planning and policies to solve the transportation problems by creating the effective and efficient public transport system. One of those was the plan of route network structuring in year 2003 by recommending the mode change policy from public transport passenger car type to be medium bus or it was known 'two in one' policy. However, it can not be applied in related and showed the controversial because it has not been accommodated the users and operators needs. This research aimed at identifying the importance level weight for each public transport component and criteria for considering in taking decision to determine the type of public transport mode in Bandar Lampung. Hence, it can support optimally the effective and efficient of public transport service. This research was conducted to obtain the importance level weight of each component and criteria for determining the mode alternative of urban public transport by using the Analytical Hierarchy Process (AHP) method. The transport elements chosen were users, operators, regulators, and transport experts, with the used criteria were travel time, waiting time, frequency, load factor, fare, reliability, safety, comfortable, and security. The sensitivity analysis was exercised for obtaining the optimal alternative by the change of scenario of the importance level weight. The results of the study showed that the determination of urban public transport type was influenced by some criteria's weight, i.e. 17.45% safety, 15.68% fare, 13.27% comfortable, 11.16% security, 10.14% waiting time, 9.15% reliability, 9.12% travel time, 7.57% frequency, and 6.47% load factor. All of those were for considering the importance level weight of 49.45% users, 28.68% operators, 14.84% regulator, and 7.04% transport expert. The third alternative as the optimal alternative was the medium bus of urban public transport of mode type chosen with capacity 30 seats for the weight of 38.29%.